Mapping the human Y chromosome by fingerprinting cosmid clones. - Taylor, K; Hornigold, N; Conway, D; Williams, D; Ulinowski, Z; Agochiya, M; Fattorini, P; de Jong, P; Little, P F; Wolfe, J (Genome Research, 1996)
We have used Y-specific cosmid clones in a random fingerprinting approach to build contigs on the human Y chromosome. Clones derived from two libraries have been analyzed. The construction of one library is described here, the second was the Y chromosome-specific library LLOYNCO3 "M" (Lawrence Livermore National Laboratory). To date, we have fingerprinted 4430 cosmids: 377 contigs have been constructed containing from 2 to 39 clones. Along with the singletons, we estimate that we have covered 72.5% of the euchomatic portion of the Y chromosome with fingerprinted clones. Sequence tagged sites are being used to anchor cosmids and contigs onto the YAC framework.